Reliability of power electronic converter systems - Chung, Henry Shu-hung; Wang, Huai (Professor in energy technology); Blaabjerg, Frede; Pecht, Michael (Institution of Engineering and Technology, 2016)
This book outlines current research into the scientific modeling, experimentation, and remedial measures for advancing the reliability, availability, system robustness, and maintainability of Power Electronic Converter Systems (PECS) at different levels of complexity.
Keywords: Electric current converters.; Reliability (Engineering); elektronické knihy; electronic books